PENGARUH PERSEPSI NILAI PELANGGAN DAN KEPUASAN KONSUMEN TERHADAP LOYALITAS KONSUMEN CITARASA BAKERY BONTANG - Sri Handayani Saleh; Tetra Tetra Hidayati; Asnawati Asnawati Asnawati (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2020)
Sri Handayani S, 2018. The influence of Customer Value Perceptions and Consumer Decisions on Citarasa Bakery Bontang Consumer Loyalty, guided by Mrs. Tetra Hidayati, SE.,M.Si as Lecturer I and Mrs. Asnawati, SE.,MM as Supervisor II. The purpose of this study was to determine the effect of Customer Value Perception and Consumer Statisfaction on Citarasa Bakery Bontang Consumer Loyalty. The analyticcal tool used in this study is multiple regression analysis consisting of Multiple Linear Regression Test, Correlation Test (R), Determination Coefficient Test (R2), F test (Simultaneous relationship analysis test), and T test (relationship analysis test Partial) using the SPSS version 20 program. The results of data analysis using SPSS resulted by regression equations as the follows: Y = 13.512 - 0,019X1 + 0,445X2  Based on the analysis results obtained simultaneously show that the perception of customer value (X1), and statisfaction (X2), has a significant effect on consumer loyalty (Y). Then partially show that the perception of customer value (X1) has no positive and insignificnt effect on consumer loyalty (Y), while the statisfaction variable (X2) has a positive and significant effect on consumer loyalty (Y)